METODE ROUGH SET UNTUK MENGANALISA PROBLEMATIKA GURU DALAM MENGGUNAKAN MEDIA PEMBELAJARAN BERBASIS KOMPUTER - wita yulianti (LPPM Universitas Abdurrab, 2016)
The development of various forms of information technology, one of them in the field of Artifici al Intelligence in the form of data mining. Data mining is a process that employs one or more computer learning techniques (a machine learning) to analyze data and extract knowledge (knowledge) automatically. Data mining is used to analyze the problems of teachers in the use of computer-based learning media. To find out the problem of teachers in the use of computer-based learning media, this study used the calculations in the form of data mining by the method of rough set. Applying data mining rough set to explore the knowledge, which is a source of information in decision making. With this method rough set problems that occurred in the teacher can be overcome in the use of computer-based learning media. Each school can determine the development of teachers in the use of learning media computer technology.